Causes of community deaths by verbal autopsy among persons with HIV in 33 districts in Zambia, 2020–2023 - Priscilla Kapombe; Choolwe Jacobs; Mark W. Tenforde; Kashala Kamalonga; Diane Morof; Terrence Lo; Mweene Cheelo; Lloyd Mulenga; Sombo Fwoloshi; Cordilia M. Himwaze; Patrick Musonda; Mpundu Makasa; et al. (PLoS ONE, 2025)
Zambia has achieved improvements in life expectancy among persons living with HIV (PLHIV) because of high antiretroviral therapy (ART) coverage, which should improve survival due to reductions in AIDS-defining conditions. However, recent estimates of the most common causes of death are not widely available. We utilized mortality surveillance data to report on common causes of death among persons with HIV who died in community settings in Zambia. The Zambian Ministry of Health conducted sentinel mortality surveillance of community deaths in 45 hospitals in 33 of 116 districts from January 2020 through December 2023. Verbal autopsies (VA) were conducted through interviews with relatives or close associates of deceased persons using the 2016 World Health Organization tool. HIV status was reported. A probable cause of death was assigned by a validated computer algorithm (InterVA5). We describe the top assigned causes of death stratified by HIV status. Verbal autopsies were conducted for 67,079 community deaths, of which 11,475 (17.1%) were persons with HIV. The mean age at death was 45 years among persons with HIV and 48 years for persons without HIV (T-test p < 0.001). The most common probable causes of death identified by VA among persons with HIV were HIV/AIDS-related causes (50.4%), cardiac disease (13.1%), pulmonary tuberculosis (7.5%), and digestive neoplasms (3.9%) . Leading probable causes in decedents without HIV were cardiac disease (24.9%), stroke (8.5%), and acute respiratory infection including pneumonia (7.6%). Overall, the percentage of deaths attributed to HIV/AIDS-related causes decreased from 11.2% to 7.5% (trend test p < 0.001) and the percentage of cardiac deaths increased from 18.7% to 25.4% (p < 0.001) from 2020 to 2023. These findings support interventions to strengthen the integrated management of noncommunicable diseases in community settings across Zambia. Among persons with HIV, a high percentage of deaths attributed to HIV/AIDS highlights the need to maintain high ART coverage and retention. Strategies, such as increased use of minimally invasive tissue sampling, may improve characterization of the high proportion of deaths attributed to non-specific HIV/AIDS-related causes through VA surveillance.